Furando a Bolha: Nudges Digitais em Sistemas de Recomendação - Alves, Gabrielle; Manzato, Marcelo G. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
This research explores the challenges of recommendation systems, focusing on diversity and bias mitigation. Excessive precision can create filter bubbles, limiting users’ worldviews and reinforcing existing preferences – a path to injustice and polarization. We investigate how nudge mechanisms can encourage interactions with diverse content, reducing biases. We analyze user interactions with recommendations, both with and without these nudges, using qualitative and quantitative methods. The results show that nudges increase diversity without compromising system quality. This research deepens the understanding of how to integrate diversity into recommendations while maintaining user satisfaction and suggests practical improvements to enhance fairness and improve the user experience.